Expressionisme in Berlijn, 1910-1920. ([S.l.] : Paleis vor schone kunsten, 1984)
Beckmann, Max ; Dix, Otto ; Grosz, George ; Heckel, Erich ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Meidner, Ludwig ; Morgner, Wilhelm ; Nolde, Emil ; Pechstein, Hermann Max ; Schmidt-Rottluff, Karl ; Steinhardt, Jakob
boek